2021
DOI: 10.1038/s41598-021-83270-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diffuse optical neuromonitoring during cardiopulmonary resuscitation predicts return of spontaneous circulation

Abstract: Neurologic injury is a leading cause of morbidity and mortality following pediatric cardiac arrest. In this study, we assess the feasibility of quantitative, non-invasive, frequency-domain diffuse optical spectroscopy (FD-DOS) neuromonitoring during cardiopulmonary resuscitation (CPR), and its predictive utility for return of spontaneous circulation (ROSC) in an established pediatric swine model of cardiac arrest. Cerebral tissue optical properties, oxy- and deoxy-hemoglobin concentration ([HbO2], [Hb]), oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Another promising application for emergent monitoring is in clinical guidance during and after cardiopulmonary resuscitation (CPR). Several studies have demonstrated that optical brain monitoring during CPR is feasible, 400 405 and recent work suggests that brain-based CPR optimization promises to enhance neurologic outcomes. In a swine model, successful resuscitation was predicted by FD-NIRS neuromonitoring.…”
Section: Clinical Applications Of Optical Spectroscopy and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising application for emergent monitoring is in clinical guidance during and after cardiopulmonary resuscitation (CPR). Several studies have demonstrated that optical brain monitoring during CPR is feasible, 400 405 and recent work suggests that brain-based CPR optimization promises to enhance neurologic outcomes. In a swine model, successful resuscitation was predicted by FD-NIRS neuromonitoring.…”
Section: Clinical Applications Of Optical Spectroscopy and Imagingmentioning
confidence: 99%
“…In a swine model, successful resuscitation was predicted by FD-NIRS neuromonitoring. 405 Encouraging associations between NIRS measures and outcomes have also been observed. [400][401][402][403] After arrest, pilot studies have explored using NIRS to individualize blood pressure targets 406,407 as well as the use of DCS measures of CBF low-frequency power 408 and pulsatility as a neurologic biomarker.…”
Section: Critical Care Managementmentioning
confidence: 99%
“…Longitudinal neurometabolic optical monitoring has elucidated risk factors for hypoxic–ischemic brain injury in several pediatric contexts, including during birth transition in healthy and high-risk neonates [ 220 , 234 240 ], and during generalized seizures [ 241 , 242 ], cardiac surgery requiring cardiopulmonary bypass [ 213 , 225 , 243 , 244 ], and extracorporeal membrane oxygenation support [ 226 , 245 ]. Quantification of oxygen delivery to the brain intra-arrest [ 246 ] (Fig. 8 ) and low-frequency blood flow oscillations post arrest [ 247 ] may provide novel noninvasive targets for physiologic optimization of resuscitation and postarrest care.…”
Section: Advances In Neuromonitoringmentioning
confidence: 99%
“…The receiver operating characteristic curve for Δ[HbO 2 ] CPR prediction of ROSC has an area under the receiver operating characteristic curve (AUC) of 0.82 (0.1) in third minute of CPR and increases to 0.97 (0.04) in the tenth minute of CPR. (Adapted from Ko et al [ 246 ] under Creative Commons CC BY license: http://creativecommons.org/licenses/by/4.0/ .) …”
Section: Advances In Neuromonitoringmentioning
confidence: 99%
“… 24 Maternal cardiac arrest requires an understanding of physiological changes during pregnancy and a modified ACLS algorithm to account for the management of 2 patients. Dr Todd Kilbaugh (University of Pennsylvania) presented on mitochondrial function in mediating neurologic outcomes in post–cardiac arrest animal models, 25 , 26 neurometabolic optical monitoring devices for cerebral metabolism, 27 and advanced approaches to neuroimaging and biomarkers for prognostication after neurologic insult. Focusing on postarrest neuroprognostication, Dr Hirsch (Stanford University) described how withdrawal of life‐sustaining treatment represents the majority of avoidable deaths because of perceptions of poor prognosis.…”
Section: Special Circumstancesmentioning
confidence: 99%